2014
DOI: 10.12693/aphyspola.125.1280
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Multilayer Nanostructured Coatings TiN/MoN Depending on Deposition Conditions

Abstract: This work presents the results of TiN/MoN coatings studying. These multilayer nanostructured coatings demonstrate dependence on depositions conditions on nanometer level. The inuence of nanosized monolayer thickness on structure changing and properties of nanocomposite multilayer coatings TiN/MoN was found. Multilayer TiN/MoN coatings of the total thickness from 6.8 to 8.2 µm were obtained using C-PVD method. Thicknesses of monolayers were 2, 10, 20, 40 nm. The structure of samples was studied using X-ray dira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…The plasticity index, which is defined as the hardness (H) to elasticity modulus (E) ratio H/E [7][8][9][10], is also rather high and exceeds the value 0.06. It allows using such coatings as protective under the influence of different alternating loadings and abrasive wear [7,[16][17][18]. For the multilayered TiN/MoN system we found that the lowest value of L c3 critical loading was 42.5 N, and it corresponds to the periodic structure with the biggest period of 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The plasticity index, which is defined as the hardness (H) to elasticity modulus (E) ratio H/E [7][8][9][10], is also rather high and exceeds the value 0.06. It allows using such coatings as protective under the influence of different alternating loadings and abrasive wear [7,[16][17][18]. For the multilayered TiN/MoN system we found that the lowest value of L c3 critical loading was 42.5 N, and it corresponds to the periodic structure with the biggest period of 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative analysis of the formulas for electric susceptibility (6) and for conductivity (7) indicates that the conductivity activation energy should be higher than the activation energy of electric susceptibility because:…”
Section: Experimental Results and Their Analysismentioning
confidence: 99%
“…As one of the most promising multilayer systems, the systems based on refractory metal nitrides or carbides, such as MoN/CrN [22], have been recently examined, since these compositions achieve high hardness and wear resistance of coatings in combination with high resistance to oxidation and other impacts of aggressive environment [23].…”
Section: Introductionmentioning
confidence: 99%